การวิเคราะห์สถานการณ์การพยาบาลเจ้าของไข้ หอผู้ป่วยหนักกุมารเวชกรรม 2 โรงพยาบาลมหาราชนครเชียงใหม่ - สุปราณี สายอุต (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Primary nursing is an individual care for patients and aims to provide holistic care and response to patient needs. The objectives of this study were to describe the situation problems, obstacles and recommendations of the primary nursing service in the Pediatric Intensive Care Unit 2 of Maharaj Nakorn Chiang Mai Hospital. The conceptual framework of this study was based on the model for primary nursing units of Marram et al. (1974) which includes: 1) primary nursing unit organization, 2) staff scheduling, 3) the distribution of work, 4) the organization of shifts for patient care continuity, 5) selection of primary patient and 6) organizational features specific to primary nursing. The population consisted of a head nurse, thirteen nurse practitioners working in the Pediatric Intensive Care Unit 2 and documents related to primary nursing. Data were collected through document reviews, interviews and focus group discussions. The data collection instruments were the semi-structured interview guidelines and focus group discussions. Data were analyzed using descriptive statistics and content analysis. The results revealed the following. 1. The situation of primary nursing in the Pediatric Intensive Care Unit 2, Maharaj Nakorn Chiang Mai Hospital was as follows: 1) primary nursing unit organization; the head nurse is the top manager of line authority and this authority can be assumed by an in–charge nurse if the head nurse is not on duty, a primary nurse coordinates patient care with a healthcare team and the patient’s family through nurses’ notes and verbal communication, 2) staff scheduling; the head nurse arranges the work schedule for primary nurses in order for them to work with their patients continuously, 3) the distribution of work; the head nurse or in-charge nurse try to assign primary nurses to take care of their patients every time they are on duty, 4) the organization of shifts for patient care continuity includes patient-data collection, assessment of patients’ problem, development of a nursing care plan, provision of care based on a nursing care plan, and shift change reports and discharge planning, 5) selection of primary patient; the head nurse or in-charge nurse selects and assigns patients to primary nurse by providing opportunities for every nurse to be a primary nurse, and 6) organizational features specific to primary nursing include family conferences and reviews of the patient care process. 2. The problems and obstacles of primary nursing included failure to assign primary nurses to their particular patient(s) every time they were on duty, incomplete patient information and discharge planning, the assignment of primary nurses did not follow the agreements, primary nurses became stressed when taking care of very sick patients for a long time, and the role of primary nurse was not clearly delineated. Primary nurses rarely had a chance to join family conferences and to perform patients’ rounds with the physician and head nurse. The suggestions were to develop a manual or a set of guidelines for primary nursing which includes a description of the role of primary nurses, patient recording, and discharge planning, care-team conference, patient rounds with physician. The guidelines need to be revised in order to consistently assign the same patient to the responsible primary nurse, and to provide consultant for primary nurses when they are stress. The results of this study can be used by nursing administrators to improve the quality of primary nursing systems and to manage problems and obstacles of primary nurses in the Pediatric Intensive Care Unit 2 of Maharaj Nakorn Chiang Mai Hospital.